1979
DOI: 10.1037/0033-2909.86.3.616
|View full text |Cite
|
Sign up to set email alerts
|

Male and female spoken language differences: Stereotypes and evidence.

Adelaide Haas

Abstract: Male speech and female speech have been observed to differ in their form, topic, content, and use. Early writers were largely introspective in their analyses; more recent work has begun to provide empirical evidence. Men may be more loquacious and directive; they use more nonstandard forms, talk more about sports, money, and business, and more frequently refer to time, space, quantity, destructive action, perceptual attributes, physical movements, and objects. Women are often more supportive, polite, and expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
90
1
2

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(114 citation statements)
references
References 42 publications
10
90
1
2
Order By: Relevance
“…The overall pattern of gender differences in conversation topics that Moore observed appears basically quite stable in subsequent studies, though Haas' (1979) prediction that conversations have changed with the times receives some support. In the studies examined here, women's share of conversations about work and money does seem to have increased since 1922, but this change is confounded with the tendency to use college-educated subjects (such as students and teachers) in recent studies.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…The overall pattern of gender differences in conversation topics that Moore observed appears basically quite stable in subsequent studies, though Haas' (1979) prediction that conversations have changed with the times receives some support. In the studies examined here, women's share of conversations about work and money does seem to have increased since 1922, but this change is confounded with the tendency to use college-educated subjects (such as students and teachers) in recent studies.…”
mentioning
confidence: 83%
“…Although Haas (1979) has suggested that gender differences in topic choice may well have changed since Moore's day, a systematic examination of trends has not been reported. Despite the considerable attention that gender differences in topic choice have received since 1922, most recent studies do not provide quantitative data about conversations held in natural settings.…”
mentioning
confidence: 99%
“…In her study of 70-year-old native Maine men and women, she found that women compared with men used many more words such as lovely, delightful, wonderful, nice, pretty, cute, dearest, gentle, gaily, beautifully, lovelies, very very, devoted, meek, perfectly wonderful, and stylish. Also, according to the studies by Brandis and Henderson and Entwisle and Garvey, girls use more adjectives than boys (Haas, 1979). In present study, after comparing the number of nouns, adjectives and verbs written by male and female adults, the researcher will classify the responses as paradigmatic and syntagmatic responses which are two word association classification types of Kess.…”
Section: Introductionmentioning
confidence: 94%
“…That is, it is hypothesized that the female participants will tend to use adjectives and verbs following nouns while most of the words written by the males are nouns and nearly none of them are adjectives and verbs, as other studies have shown (Wang and Shelley, 2007). Lakoff's hypothesis is that women use evaluative adjectives more than men (Haas, 1979). Hartman (1976) tested and supported Lakoff's hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…analytical and logical and females are more subjective and intuitive (Haas, 1979). Also, males use self-generated information and females use self-as well as other-generated information (Hunt and Einstein, 1981).…”
Section: The Effect Of Cultural and Demographic Factors On The Percepmentioning
confidence: 99%